Quantifying written law: A new fiscal rule index for Swiss cantons - Philipp Weber (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2025)
To consider legal standards in empirical research designs, the qualitative information of the law needs to be transferred in a numerical variable. The challenge in creating such a variable consists in finding the right balance between high information density and transparency while keeping the scope for sub- jective decisions to a minimum. This paper provides for a novel evaluation framework of this task that is applicable to different forms of written law. The collected data is transformed to an index variable using four distinct aggregation techniques (discretionary weighting, optimized weighting, variation maximization weighting, and rank orders). These techniques are evaluated by variance and sensitivity analyses and compared against well-established datasets. All three steps - conceptualization, aggrega- tion, and evaluation - are exemplified by deriving a new fiscal rule index for Swiss cantons for the observation period 2007 to 2021.
Keywords: C43; C82; E62; H61; H72; 330; Index Numbers and Aggregation; Data Collection; Budget System; Law and Economics